Endocrine surgery in the Coronavirus disease 2019 pandemic: Surgical Triage Guidelines. Issue 6 (30th April 2020) - Jozaghi, Yelda; Zafereo, Mark E.; Perrier, Nancy D.; Wang, Jennifer R.; Grubbs, Elizabeth; Gross, Neil D.; Fisher, Sarah; Sturgis, Erich M.; Goepfert, Ryan P.; Lai, Stephen Y.; Best, Conor; Busaidy, Naifa L.; et al.
Abstract: Background: In the face of the COVID‐19 pandemic, cancer care has had to adapt rapidly given the Centers for Disease Control and Prevention and the American College of Surgeons (ACS) issuing recommendations to postpone nonurgent surgeries. Methods: An institutional multidisciplinary group of Head and Neck Surgical Oncology, Surgical Endocrinology, and Medical Endocrinology devised Surgical Triaging Guidelines for Endocrine Surgery during COVID‐19, aligned with phases of care published by the ACS. Results: Phases of care with examples of corresponding endocrine cases are outlined. Most cases can be safely postponed with active surveillance, including most differentiated and medullary thyroid cancers. During the most acute phase, all endocrine surgeries are deferred, except thyroid tumors requiring acute airway management. Conclusions: These guidelines provide context for endocrine surgery within the spectrum of surgical oncology, with the goal of optimal individualized multidisciplinary patient care and the expectation of significant resource diversion to care for patients with COVID‐19.